Intra-individual Variation in Language - Auer, Anita; Britain, David; Büchler, Andrin; Bülow, Lars; Ellsäßer, Sophie; Entringer, Nathalie; Fanta-Jende, Johanna; Havinga, Anna D.; Merten, Marie-Luis; Nickel, Grit; Pfenninger, Simone E.; Pröll, Simon; et al. (Trends in linguistics. Studies and monographs ;, 2021)
This volume offers several empirical, methodological, and theoretical approaches to the study of observable variation within individuals on various linguistic levels. With a focus on German varieties, the chapters provide answers on the following questions (inter alia):Which linguistic and extra-linguistic factors explain intra-individual variation? Is there observable intra-individual variation that cannot be explained by linguistic and extra-linguistic factors? Can group-level results be generalised to individual language usage and vice versa? Is intra-individual variation indicative of actual patterns of language change? How can intra-individual variation be examined in historical data?Consequently, the various theoretical, methodological and empirical approaches in this volume offer a better understanding of the meaning of intra-individual variation for patterns of language development, language variation and change.The inter- and transdisciplinary nature of the volume is an exciting new frontier, and the results of the studies in this book provide a wealth of new findings as well as challenges to some of the existing findings and assumptions regarding the nature of intra-individual variation.